Assessment of failure mechanisms in deep longwall faces based on mining-induced seismicity - Mahdevari, S.; Shahriar, K.; Sharifzadeh, Mostafa; Tannant, D. (Springer, 2016)
Failure mechanisms of the rock mass in the regions of maximum stress concentrations around a longwall face were assessed. In this respect, seismic events that result from changes in the stress field were analyzed to gain more knowledge about rock failure mechanisms in the proximity of the face area. A deep longwall mine developed at depths of about 3–3.5 km in South Africa was selected as a case study. Seismic moment tensor solutions were obtained for 32 seismic events with moment magnitudes in the range of 0.49 and 2.10. Through moment tensor decomposition, the dominant failure mechanisms were investigated by drawing focal mechanism plots. Further analysis was implemented by depicting the corresponding 3D radiation patterns of P-wave particle motions. Although the results cover various failure mechanisms, the dominant mechanisms are shear, implosional, and compressional failures. According to the results, most of the maximum principal stresses in the mine are compressive and oriented nearly vertical, which are in accordance with the gravitational collapses of the mined out areas. The results obtained from this research show that measuring and analyzing mining-induced seismicity can be a reliable measure to characterize the dominant failure mechanisms in a nondestructive manner and to provide a useful assessment of the stability of the longwall face in advance of extraction.